(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Dilated cardiomyopathy (DCMP) is a diffuse myocardial lesion with dilatation (dilation) of the heart cavities and a sharp decrease in its contractile function. DCMP is a common pathology and occurs in the world with a frequency of 5-8 cases per 100000 population. In particular, 36 cases per 100000 population are registered in the USA. Male persons are more often affected (2:10), clinical manifestations of the disease occur at the age of 10 to 30 years. The incidence of DCMP is 2.5 times higher in negroid males than in Caucasians and females. The prognosis of the disease becomes unfavorable when patients have heart failure, which in turn makes this pathology threatening to the life of the patient. The lethality rate ranges from 25% to 30% per year. In 5 years from the onset of the disease, 60-75% of patients with DCMP practically die. The classification of DCMP approved by the American Heart Association in 2006 is most often used in physician practice. In this classification, the AHA proposed the definition of CMP as "a heterogeneous group of myocardial diseases associated with mechanical or electrical dysfunction, which usually manifest with inadequate hypertrophy or dilatation and arise from a variety of causes that are often genetic. CMP is confined to the heart or is part of generalized systemic disorders, always leading to cardiovascular death or progression of heart failure.".